2023
DOI: 10.1186/s12905-023-02248-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to interparental violence and justification of intimate partner violence among women in Papua New Guinea

Abstract: Background Previous studies have demonstrated that exposure to interparental violence is associated with intimate partner violence justification in a variety of contexts. In this study, we examined the association between exposure to interparental violence and justification of intimate partner violence among women in Papua New Guinea. Methods We used data from the 2016–18 Papua New Guinea Demographic and Health Survey. We included 2839 women of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…For instance, husbands' drinking habits, which are known to promote IPV (Shaikh 2022;Solanke 2018;Tlapek 2015), were not investigated in the IDHS questionnaire as most Indonesians do not consume alcohol because of their religious beliefs. Exposure to interparent violence during childhood, which has been linked to IPV experiences and attitudes in adulthood (Aboagye et al 2023;Hindin et al 2008;Solanke 2018), was also excluded. Therefore, this aspect was not examined in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, husbands' drinking habits, which are known to promote IPV (Shaikh 2022;Solanke 2018;Tlapek 2015), were not investigated in the IDHS questionnaire as most Indonesians do not consume alcohol because of their religious beliefs. Exposure to interparent violence during childhood, which has been linked to IPV experiences and attitudes in adulthood (Aboagye et al 2023;Hindin et al 2008;Solanke 2018), was also excluded. Therefore, this aspect was not examined in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Julio et al (2023) indicated that maternal exposure to physical violence and controlling behavior by an intimate partner affects children's physical development and cognitive abilities. In addition, if women were exposed to interparental violence in childhood, they are more likely to justify IPV later in life (Aboagye et al 2023) and become victims of violence perpetrated by their intimate partners (Hindin et al 2008;Solanke 2018). Furthermore, several empirical studies have revealed a significant relationship between women's positive attitudes toward male-perpetrated IPV and the likelihood of being a victim of IPV caused by their husbands or partners (Benebo et al 2018;Khawaja et al 2008;Shaikh 2022;Solanke 2018;Tlapek 2015).…”
Section: Introductionmentioning
confidence: 99%